Positive electrode active material for lithium-ion secondary batteries

A tailored positive electrode active material with specific particle compositions and sizes addresses the challenge of maintaining high energy density and safety in lithium ion secondary batteries by stabilizing the crystal structure and reducing voids, thereby enhancing thermal stability.

JP7602359B2Active Publication Date: 2024-12-18TAIHEIYO CEMENT CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020205253
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-10
Publication Date
2024-12-18
Estimated Expiration
2040-12-10

AI Technical Summary

Technical Problem

Existing lithium ion secondary batteries using layered lithium composite oxides face challenges in maintaining high energy density per volume while ensuring safety, particularly due to the elution of transition metals into the electrolyte, which affects cycle characteristics and thermal stability.

Method used

A positive electrode active material composed of specific particles with formulas (A), (B), and (C) in defined proportions, including LiNi a Co b Mn c M 1 w O 2, Li f Mn g Fe h M 2 x P.O. 4, and LiM 3 y Co j O 2, with controlled particle sizes and compositions, to enhance energy density and safety by reducing voids and stabilizing the crystal structure.

Benefits of technology

The proposed active material effectively increases energy density per volume and ensures excellent safety by minimizing particle expansion and contraction, preventing crystal structure collapse, and enhancing thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602359000002
    Figure 0007602359000002
  • Figure 0007602359000003
    Figure 0007602359000003
  • Figure 0007602359000001
    Figure 0007602359000001
Patent Text Reader

Abstract

To provide a positive electrode active material for a lithium-ion secondary battery capable of sufficiently increasing both the energy density per volume and the safety.SOLUTION: A positive electrode active material for a lithium-ion secondary battery includes a component (A) having 40 mass% to 85 mass% of particles represented by the formula (a) of LiNiaCobMncM1wO2 and having an average particle size of 5 μm to 15 μm, a component (B) having 10 mass% to 30 mass% of particles represented by the formula (b) of LifMngFehM2xPO4 and having an average particle size of 12 μm to 25 μm, and a component (C) having 5 mass% to 40 mass% of particles represented by the formula (c) of LiM3yCojO2 and having an average particle size of 2 μm to 8 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, for obtaining a lithium ion secondary battery having excellent energy density per volume and safety. [Background technology]

[0002] Layered lithium composite oxides, such as layered lithium-nickel-cobalt-manganese composite oxide (NMC), have a layered crystal structure in which lithium atomic layers and transition metal atomic layers are alternately stacked with oxygen atomic layers in between. Such layered lithium composite oxides are used as positive electrode active materials that can be used to construct high-power and high-capacity lithium-ion secondary batteries.

[0003] In lithium-ion secondary batteries using such layered lithium composite oxides as the positive electrode active material, charging and discharging are performed by the desorption and insertion of lithium ions into the layered lithium composite oxides. However, as the charge and discharge cycles are repeated, the capacity decreases, and especially when used for a long period of time, the capacity of the battery may decrease significantly. This is thought to be due to the fact that the transition metal components of the lithium composite oxide dissolve into the electrolyte during charging, making the crystal structure more likely to collapse. In particular, the higher the temperature, the more the transition metal dissolves, and the greater the impact on cycle characteristics. In addition, if the crystal structure of the lithium composite oxide collapses, the transition metal components of the lithium composite oxide dissolve into the surrounding electrolyte, which may reduce the thermal stability and compromise safety.

[0004] Under these circumstances, various developments have been made using highly useful layered lithium composite oxides. For example, Patent Document 1 describes a lithium-ion battery having the formula Li x Co a M1 b O2 and a compound represented by the formula Li y Ni 1-c-d Co c Mn d M2 eIn addition, Patent Document 2 discloses a non-aqueous electrolyte battery having a positive electrode layer containing a compound represented by LiO2, and attempts have been made to improve the discharge characteristics at low temperatures. 1+x A positive electrode active material for lithium ion secondary batteries containing MPO4 (0≦x≦1, M is one or more elements selected from Fe, Mn, etc.) has been disclosed, which aims to improve input characteristics while ensuring safety. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-60020 A [Patent Document 2] JP 2016-76317 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, even with the technology described in Patent Document 1, it is not certain whether it is possible to sufficiently increase the energy density per volume while ensuring safety (thermal stability, hereinafter the same), and even with the technology described in Patent Document 2, sufficient consideration has not been given to increasing the energy density per volume, and there is still room for improvement in order to achieve both safety and safety.

[0007] Therefore, an object of the present invention is to provide a positive electrode active material for a lithium ion secondary battery that can sufficiently increase both the energy density per volume and the safety. [Means for solving the problem]

[0008] Therefore, as a result of intensive studies to solve the above problems, the present inventors have found a positive electrode active material for a lithium ion secondary battery that can sufficiently increase both the energy density per volume and the safety in the obtained lithium ion secondary battery by containing specific particles represented by a specific formula in specific amounts respectively.

[0009] That is, the present invention relates to the following components (A), (B), and (C): (A) 40% to 85% by mass of particles represented by the following formula (a) and having an average particle diameter of 5 μm to 15 μm LiNi a Co b Mn c M 1 w O2···(a) (In formula (a), M 1 represents one or more elements selected from Mg, Ti, Nb, Fe, Cr, Si, Al, Ga, V, Zn, Cu, Sr, Mo, Zr, Sn, Ta, W, La, Ce, Pb, Bi, and Ge. a, b, c, w are numbers satisfying 0.3 ≦ a < 1, 0 < b ≦ 0.7, 0 < c ≦ 0.7, 0 ≦ w ≦ 0.3, and 3a + 3b + 3c + (valence of M 1 ) × w = 3. ) (B) 10% to 30% by mass of particles represented by the following formula (b) and having an average particle diameter of 12 μm to 25 μm Li f Mn g Fe h M 2 x PO4···(b) (In formula (b), M 2 represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd. f, g, h, and x are numbers satisfying 0 < f ≦ 1.2, 0.3 ≦ g ≦ 1.2, 0.2 ≦ h ≦ 1.2, 0 ≦ x ≦ 0.3, and 3 / 7 ≦ g / h ≦ 4, and f + (valence of Mn) × g + (valence of Fe) × h + (valence of M 2 ) × x = 3. ) (C) Particles represented by the following formula (c) and having an average particle size of 2 μm to 8 μm, 5% by mass to 40% by mass LiM 3 y Co j O2 ··· (c) (In formula (c), M 3 represents one or more elements selected from Ni, Mn, Al, Mg, Ti, V, Cr, Fe, Zr, Ga, and Si. y and j are numbers satisfying 0 ≤ y ≤ 0.1, 0 < j ≤ 1, and (valence of M 3 ) × y + 3j = 3.) It provides a positive electrode active material for a lithium - ion secondary battery containing

Advantages of the Invention

[0010] According to the positive electrode active material for a lithium - ion secondary battery of the present invention, a lithium - ion secondary battery with effectively increased energy density per unit volume and excellent safety (thermal stability) can be realized.

Brief Description of the Drawings

[0011] [Figure 1] It is an SEM image showing a part of the particles (B1) obtained in Production Example 2. [Diagram 2] It is a distribution diagram obtained in the measurement of pore distribution by mercury intrusion porosimetry of the particles (B1) obtained in Production Example 2.

Modes for Carrying Out the Invention

[0012] Hereinafter, the present invention will be described in detail. The positive electrode active material for a lithium - ion secondary battery of the present invention comprises the following components (A), (B), and (C): (A) Particles represented by the following formula (a) and having an average particle size of 5 μm to 15 μm, 40% by mass to 85% by mass LiNi a Co b Mn c M 1 w O2 ··· (a) (In formula (a), M1 represents one or more elements selected from Mg, Ti, Nb, Fe, Cr, Si, Al, Ga, V, Zn, Cu, Sr, Mo, Zr, Sn, Ta, W, La, Ce, Pb, Bi, and Ge. a, b, c, and w satisfy 0.3 ≦ a < 1, 0 < b ≦ 0.7, 0 < c ≦ 0.7, 0 ≦ w ≦ 0.3, and 3a + 3b + 3c + (valence of M 1 ) × w = 3. (B) Particles represented by the following formula (b) and having an average particle size of 12 μm to 25 μm, 10% by mass to 30% by mass Li f Mn g Fe h M 2 x PO4···(b) (In formula (b), M 2 represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd. f, g, h, and x satisfy 0 < f ≦ 1.2, 0.3 ≦ g ≦ 1.2, 0.2 ≦ h ≦ 1.2, 0 ≦ x ≦ 0.3, and 3 / 7 ≦ g / h ≦ 4, and f + (valence of Mn) × g + (valence of Fe) × h + (valence of M 2 ) × x = 3. (C) Particles represented by the following formula (c) and having an average particle size of 2 μm to 8 μm, 5% by mass to 40% by mass LiM 3 y Co j O2···(c) (In formula (c), M 3 represents one or more elements selected from Ni, Mn, Al, Mg, Ti, V, Cr, Fe, Zr, Ga, and Si. y and j satisfy 0 ≦ y ≦ 0.1, 0 < j ≦ 1, and (valence of M 3 ) × y + 3j = 3. contains.

[0013] In this way, since the positive electrode active material for lithium ion secondary batteries of the present invention contains specific amounts of each of the three specific types of particles represented by the above specific formula, it is possible to improve safety in the resulting lithium ion secondary battery without unnecessarily reducing the energy density per volume, and it is also possible to effectively reduce the voids between the particles to further increase the energy density per volume (hereinafter also abbreviated as "energy density").

[0014] The positive electrode active material for a lithium ion secondary battery of the present invention contains, as component (A), 40% by mass to 85% by mass of particles represented by the following formula (a) and having an average particle size of 5 μm to 15 μm. LiNi a Co b Mn c M 1 w O2 (a) (In formula (a), M 1 represents one or more elements selected from Mg, Ti, Nb, Fe, Cr, Si, Al, Ga, V, Zn, Cu, Sr, Mo, Zr, Sn, Ta, W, La, Ce, Pb, Bi, and Ge. a, b, c, and w are within the range of 0.3≦a<1, 0 <b≦0.7、0<c≦0.7、0≦w≦0.3、かつ3a+3b+3c+(M 1 The number that satisfies (valence of x) × w = 3.

[0015] The particles of component (A) represented by the above formula (a) are lithium composite oxide particles (so-called Li-Ni-Co-Mn oxide particles (NCM particles), hereinafter also referred to as "particles (A)"), which are particles having a layered rock salt structure and are secondary particles formed by aggregation of primary particles. By containing such component (A) having a specific average particle size in the above amount, it is possible to effectively reduce the voids between the particles of components (B) and (C) described below while maintaining excellent safety, thereby contributing to improving the energy density.

[0016] M in formula (a) 1represents one or more elements selected from Mg, Ti, Nb, Fe, Cr, Si, Al, Ga, V, Zn, Cu, Sr, Mo, Zr, Sn, Ta, W, La, Ce, Pb, Bi, and Ge. In addition, a, b, c, and w in the above formula (a) are within the range of 0.3≦a<1, 0 <b≦0.7、0<c≦0.7、0≦w≦0.3、かつ3a+3b+3c+(M 1 It is a number that satisfies (valence of x) × w = 3.

[0017] In the particles (A) represented by the above formula (a), Ni, Co and Mn are known to have excellent electronic conductivity and contribute to the battery capacity and output characteristics. From the viewpoint of safety, it is also preferable that a part of such transition elements is mixed with other metal elements M 1 It is preferable that these metal elements M 1 By replacing the compound by the formula (a), the crystal structure of the particle (A) represented by the formula (a) is stabilized, so that destruction of the crystal structure can be suppressed even when the compound is repeatedly charged and discharged, and excellent safety can be ensured.

[0018] Specific examples of the NCM particles represented by the above formula (a) include LiNi 0.33 Co 0.33 Mn 0.34 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.2 Co 0.4 Mn 0.4 O2, LiNi 0.33 Co 0.31 Mn 0.33 Mg 0.03 O2 or LiNi 0.33 Co 0.31 Mn 0.33 Zinc 0.03 O2, etc. Among them, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.33 Co0.33 Mn 0.34 O2, LiNi 0.33 Co 0.31 Mn 0.33 Mg 0.03 Particles made of O2 are preferred.

[0019] Furthermore, the particles (A) represented by the above formula (a) of two or more different compositions may form a core-shell structure having a core part (inside) and a shell part (surface part). By forming the particles (A) with this core-shell structure, NCM-based composite oxide particles with a high Ni concentration that are easily dissolved in the electrolyte can be arranged in the core part, and NCM-based composite oxide particles with a low Ni concentration can be arranged in the shell part that contacts the electrolyte, so that it is possible to suppress the deterioration of cycle characteristics and to further improve safety. In this case, the core part may be one phase, or may be composed of two or more phases with different compositions. As an embodiment in which the core part is composed of two or more phases, it may be a structure in which a plurality of phases are concentrically layered, or a structure in which the composition changes transitionally from the surface of the core part toward the center part. Furthermore, the shell portion may be any portion formed on the outside of the core portion, and may be a single phase like the core portion, or may be composed of two or more phases with different compositions.

[0020] As the particle (A) having a core-shell structure formed by two or more kinds of NCM particles having different compositions, specifically, the (core portion)-(shell portion) is, for example, (LiNi 0.8 Co 0.1 Mn 0.1 O2)-(LiNi 0.2 Co 0.4 Mn 0.4 O2), (LiNi 0.8 Co 0.1 Mn 0.1 O2)-(LiNi 0.33 Co 0.33 Mn 0.34 O2), or (LiNi 0.8 Co 0.1 Mn 0.1 O2)-(LiNi 0.33 Co 0.31 Mn 0.33 Mg0.03 Examples of particles include those made of oxygen (O2).

[0021] Furthermore, the particles (A) represented by the above formula (a) may be coated with a metal oxide, a metal fluoride, or a metal phosphate. By coating the NCM particles with these metal oxides, metal fluorides, or metal phosphates, the metal components (Ni, Mn, Co, Mn) from the NCM particles to the electrolyte can be prevented from being transferred to the electrolyte. 1 As such a coating, one or more selected from CeO2, SiO2, MgO, Al2O3, ZrO2, TiO2, ZnO, RuO2, SnO2, CoO, Nb2O5, CuO, V2O5, MoO3, La2O3, WO3, AlF3, NiF2, MgF2, LiF, Li3PO4, Li4P2O7, LiPO3, Li2PO3F, and LiPO2F2, or a composite thereof, can be used.

[0022] The average particle size of the primary particles of the particles (A) represented by the above formula (a) is preferably 50 nm to 500 nm, more preferably 50 nm to 300 nm, from the viewpoints of suppressing the amount of expansion and contraction of the primary particles accompanying insertion and desorption of lithium ions, effectively preventing particle cracking, and handling. Here, the "average particle size as primary particles" of the particles (A) means the crystallite size measured by X-ray diffraction method. Furthermore, the average particle size of the particles (A), which are secondary particles formed by aggregation of the primary particles (simply referred to as the "average particle size of the particles (A)") is 5 μm to 15 μm, and preferably 8 μm to 12 μm, from the viewpoint of obtaining a battery with excellent safety and from the viewpoint of handling. Here, the "average particle size" of the particles (A) is the D obtained from the volume-based particle size distribution based on the laser diffraction / scattering method. 50 The values ​​shown are the particle diameters (median diameters) at 50% of the cumulative particle size.

[0023] From the viewpoint of effectively achieving both high energy density and excellent safety, the content of component (A) (particles (A)) in the positive electrode active material for a lithium ion secondary battery of the present invention is 40 mass % to 85 mass %, preferably 45 mass % to 80 mass %, and more preferably 50 mass % to 70 mass %.

[0024] The particles (A) can be obtained, for example, by the following production method. Specifically, the production method includes a step (Ia) of preparing slurry water a by adding a nickel compound, a cobalt compound, a manganese compound, and water, filtering and drying the slurry water a to obtain mixture A, and a step (IIa) of adding a lithium compound to the obtained mixture A, mixing the mixture, and then calcining the mixture.

[0025] The nickel compound used in step (Ia) includes nickel sulfate, nickel acetate, etc., which may be used alone or in combination of two or more. Among them, nickel sulfate is preferred from the viewpoint of improving the battery characteristics. Examples of the cobalt compound include cobalt acetate, cobalt nitrate, and cobalt sulfate. These may be used alone or in combination of two or more. Among these, cobalt sulfate is preferred from the viewpoint of improving battery characteristics. Examples of manganese compounds include manganese acetate, manganese nitrate, manganese sulfate, etc. These may be used alone or in combination of two or more. Among these, manganese sulfate is preferred from the viewpoint of improving battery characteristics. In addition to these nickel compounds, cobalt compounds, and manganese compounds, metals other than these compounds (M 1 ) compounds may also be used. Examples of lithium compounds include hydroxides (e.g., LiOH·H2O, LiOH), carbonates, sulfates, and acetates. Of these, carbonates are preferred.

[0026] In step (Ia), when obtaining the slurry water a, it is preferably adjusted to a pH of 8 to 13, and for example, it may be adjusted by dropping ammonia water.

[0027] In step (IIa), when firing, first pre-firing is carried out at 500°C to 1000°C, preferably 600°C to 900°C for 1 hour to 15 hours, preferably 1 hour to 6 hours, and then main firing is carried out at 500°C to 1000°C, preferably 600°C to 900°C for 1 hour to 15 hours, preferably 5 hours to 13 hours. Also, it is preferably crushed after pre-firing and then subjected to main firing.

[0028] The positive electrode active material for a lithium ion secondary battery of the present invention contains, as component (B), particles represented by the following formula (b) and having an average particle size of 12 μm to 25 μm in an amount of 10% by mass to 30% by mass. Li f Mn g Fe h M 2 x PO4···(b) (In formula (b), M 2 represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd. f, g, h, and x satisfy 0 < f ≦ 1.2, 0.3 ≦ g ≦ 1.2, 0.2 ≦ h ≦ 1.2, 0 ≦ x ≦ 0.3, and 3 / 7 ≦ g / h ≦ 4, and f + (valence of Mn) × g + (valence of Fe) × h + (valence of M 2 represents a number that satisfies ) × x = 3.

[0029] The particles of component (B) represented by the above formula (b) are olivine-type lithium transition metal phosphate compounds (so-called LMFP particles, hereinafter also referred to as "particles (B)") that contain at least both manganese (Mn) and iron (Fe) as transition metals, and are secondary particles formed by aggregation of primary particles. Component (B) has a specific average particle size and is relatively more easily deformed than other components, and by including this in the above amount, in combination with component (A), it is possible to effectively increase safety without unnecessarily decreasing the energy density.

[0030] From the viewpoint of the average discharge voltage, the above particles (B) are preferably 0.6≦f≦1.2 for f, more preferably 0.65≦f≦1.15, and even more preferably 0.7≦f≦1.1 for g. The preferred range is 0.4≦g≦0.8, more preferably 0.5≦g≦0.8, and even more preferably 0.7≦g≦0.8 for h. The preferred range is 0.2≦h≦0.6, more preferably 0.2≦h≦0.5, and even more preferably 0.2≦h≦0.3 for h. The preferred range is 0≦x≦0.2, more preferably 0≦x≦0.15, and even more preferably 0≦x≦0.1 for x. And, g / h is the molar ratio of Mn and Fe constituting the so-called particles (B), and is preferably 2 / 3≦g / h≦4, more preferably 1≦g / h≦4, and even more preferably 3 / 2≦g / h≦4.

[0031] Specifically, for example, LiMn 0.3 Fe 0.7 PO4, LiMn 0.7 Fe 0.3 PO4, LiMn 0.9 Fe 0.1 PO4, LiMn 0.8 Fe 0.2 PO4, LiMn 0.75 Fe 0.15 Mg 0.1 PO4, LiMn 0.75 Fe 0.19 Zr 0.03 PO4, LiMn 0.6 Fe 0.4 PO4, LiMn 0.5 Fe 0.5 PO4, Li1.2 Mn 0.63 Fe 0.27 PO4, Li 0.6 Mn 0.84 Fe 0.36 PO4, etc. Among them, LiMn 0.3 Fe 0.7 PO4, LiMn 0.7 Fe 0.3 PO4, LiMn 0.8 Fe 0.2 PO4, LiMn 0.6 Fe 0.4 PO4, Li 1.2 Mn 0.63 Fe 0.27 PO4 or Li 0.6 Mn 0.84 Fe 0.36 PO4 is preferred.

[0032] The average particle size of the primary particles of the particles (B) represented by the above formula (b) is preferably 50 nm to 250 nm, more preferably 100 nm to 150 nm, from the viewpoints of suppressing the amount of expansion and contraction of the primary particles accompanying insertion and desorption of lithium ions, effectively preventing particle cracking, and handling. Here, the "average particle size as primary particles" of the particles (B) means the crystallite size measured by X-ray diffraction method. Moreover, the average particle size of particles (B), which are secondary particles formed by aggregation of the primary particles, (simply referred to as "average particle size of particles (B)") is 12 μm to 25 μm, preferably 12 μm to 20 μm, and more preferably 12 μm to 18 μm, from the viewpoint of effectively increasing the energy density and from the viewpoint of handling. Here, the "average particle size" of the particles (B) is the D obtained from the volume-based particle size distribution based on the laser diffraction / scattering method. 50 The values ​​shown are the particle diameters (median diameters) at 50% of the cumulative particle size.

[0033] From the viewpoint of effectively increasing both the energy density and safety, the particles (B) represented by the above formula (b) are preferably particles that are easily deformed, i.e., particles that exhibit the physical property of being easily crushed. Specifically, the particles (B) are a particle aggregate including particles having one to two dents formed on the surface, and the particles (B) as a whole have a mode of dent diameter of 1.0 μm to 4.0 μm, a dent volume of 0.2 mL / g to 0.8 mL / g, and a compaction degree of 2.5 g / cm under a load of 20 kN, as measured by mercury intrusion porosimetry. 3 ~3.3g / cm 3 That is, it is preferable that the particles (B) contain, as a part of the particles constituting the particles, particles having one to two large dents on their surfaces, and that the particle aggregate as a whole exhibits the above-mentioned high mode of dent diameter and dent volume measured by mercury intrusion porosimetry, and has an appropriate strength that easily deforms to avoid collapse while suppressing excessive pulverization.

[0034] The "depression" formed on the surface of a part of the particles included in the particle (B) means a concave portion in which the particle surface deviates from the imaginary surface and sinks toward the inside of the particle when the whole particle is regarded as a sphere and the surface of the sphere is taken as an imaginary surface. Such a "depression" is a concave portion large enough to be recognized, for example, in a SEM photograph. The "dent diameter" refers to the diameter of a perfect circle drawn by connecting the points where the deviation of the particle surface from the virtual surface begins, and the "mode of dent diameter" corresponds to the average value of the "dent diameters" and is a value that serves as an index for recognizing the size of the "dents." In the present invention, the so-called pore diameter measured by mercury intrusion porosimetry for the entire particle (B) is defined as the "dent diameter," and the peak value obtained from a pore diameter distribution diagram is defined as the "mode of dent diameter." Furthermore, the "depression volume" is the volume occupied by the "depressions" and is equivalent to the value obtained by subtracting the volume of the particle having the depressions formed therein from the volume of the assumed sphere. In the present invention, the "depression volume" is defined as the peak area of ​​the pore size distribution diagram measured by mercury intrusion porosimetry for the entire particle (B). Incidentally, particles having one or two depressions formed on the surface are also so-called secondary particles formed by aggregation of the above-mentioned primary particles.

[0035] Such particles (B) can exhibit high compaction properties, and by containing them together with the above particles (A) and particles (C) described below under specified conditions to form a positive electrode active material for a lithium ion secondary battery, it is possible to improve safety without unnecessarily reducing the energy density, and also to effectively reduce the voids between the particles to further increase the energy density.

[0036] The mode of the dent diameter in the particles (B) measured by mercury intrusion porosimetry is from 1.0 μm to 4.0 μm, preferably from 1.0 μm to 3.0 μm, and more preferably from 1.0 μm to 2.5 μm. The dent volume of the particles (B) measured by mercury intrusion porosimetry (dent volume per 1 g of particles (B)) is 0.2 mL / g to 0.8 mL / g, preferably 0.25 mL / g to 0.8 mL / g, and more preferably 0.3 mL / g to 0.8 mL / g.

[0037] The particles (B) can be easily compacted to show a high degree of compaction, and therefore the degree of compaction under a load of 20 kN is 2.5 g / cm 3 ~3.3g / cm 3 and preferably 2.7 g / cm 3 ~3.3g / cm 3 and more preferably 2.9 g / cm 3 ~3.3g / cm 3 It is.

[0038] The tap density of the particles (B) is preferably 0.7 g / cm3 from the viewpoint that some of the particles constituting the particles (B) are large particles having large depressions on the surface. 3 ~1.1g / cm 3 and more preferably 0.7 g / cm 3 ~1.0g / cm 3 and more preferably 0.7 g / cm 3 ~0.9g / cm 3It is. The tap density means the "tap bulk density" measured by the method specified in JIS R 1628 "Method of measuring bulk density of fine ceramic powders."

[0039] In particles (B), the proportion of particles having one to two dents formed on the surface thereof exhibits the above-mentioned mode of dent diameter and dent volume, and from the viewpoint of imparting a high degree of compaction that allows easy compaction, is preferably 30% to 100% of the total number of particles (B) (total number of particles (B)). The percentage of particles having one or two dents on their surface in all particles (B) can be determined by observing with an electron microscope and calculating the value (%) of {(number of particles having one or two dents with a diameter of 1.0 μm or more on their surface) / (total number of particles with a diameter of 5.0 μm or more)}×100.

[0040] From the viewpoint of ensuring an excellent discharge capacity, the particles (B) may be particles having carbon derived from cellulose nanofibers and / or carbon derived from a water-soluble carbon material supported on the surface of the particles. Cellulose nanofibers are a skeletal component that accounts for about 50% of all plant cell walls, and are lightweight, high-strength fibers that can be obtained by defibrating the plant fibers that make up such cell walls to nano-size. The fiber diameter of such cellulose nanofibers is 1 nm to 1000 nm, and they also have good dispersibility in water. In addition, a periodic structure of carbon is formed in the cellulose molecular chains that make up the cellulose nanofibers. Therefore, when such cellulose nanofibers are carbonized to become carbon and are firmly supported on the surface of the above-mentioned particles (B), the particles (B) exhibit physical properties that make them easy to crush, but have appropriate strength that easily deforms to avoid collapse and suppress excessive pulverization, and effectively suppress the decrease in the electronic conductive path and effectively increase the degree of compaction, thereby ensuring the expression of excellent discharge capacity in the resulting battery.

[0041] When carbon derived from cellulose nanofibers is supported on the surface of particles (B), the atomic amount of carbon derived from the carbonized cellulose nanofibers, i.e., the amount of carbon derived from the cellulose nanofibers supported, based on 100% by mass of particles (B), is preferably 0.1% by mass to 10.0% by mass, more preferably 0.1% by mass to 7.0% by mass, and even more preferably 0.1% by mass to 5.0% by mass.

[0042] The water-soluble carbon material, like the cellulose nanofibers, is carbonized to become carbon, and when this is supported on the surface of the particles (B), like the cellulose nanofibers, it effectively suppresses the deterioration of the electronic conductive path and effectively increases the compaction degree, thereby ensuring the expression of excellent discharge capacity in the resulting battery. Examples of such water-soluble carbon materials include one or more selected from sugars, polyols, polyethers, and organic acids. More specifically, examples include monosaccharides such as glucose, fructose, galactose, and mannose; disaccharides such as maltose, sucrose, and cellobiose; polysaccharides such as starch and dextrin; polyols and polyethers such as ethylene glycol, propylene glycol, diethylene glycol, polyethylene glycol, butanediol, propanediol, polyvinyl alcohol, and glycerin; and organic acids such as citric acid, tartaric acid, and ascorbic acid. Among these, from the viewpoint of increasing the solubility and dispersibility in a solvent to effectively function as a carbon material, glucose, fructose, sucrose, and dextrin are preferred, and glucose is more preferred.

[0043] When carbon derived from a water-soluble carbon material is supported on the surface of the particles (B), the atomic amount of carbon derived from the water-soluble carbon material, i.e., the amount of carbon derived from the water-soluble carbon material supported, in 100 mass% of the particles (B), is preferably 0 mass% to 4.0 mass%, more preferably 0 mass% to 3.0 mass%, and even more preferably 0 mass% to 2.0 mass%.

[0044] Regarding the carbon derived from the cellulose nanofibers and the carbon derived from the water-soluble carbon material, only the carbon derived from the cellulose nanofibers, only the carbon derived from the water-soluble carbon material, or both the carbon derived from the cellulose nanofibers and the carbon derived from the water-soluble carbon material may be supported. Of these, it is preferable to support the carbon derived from the cellulose nanofibers, from the viewpoint of covering only a part of the surface of the particles (B) and not preventing the deformation of the particles (B).

[0045] When carbon derived from cellulose nanofibers and carbon derived from a water-soluble carbon material are supported on the surface of particles (B), the sum of the atomic equivalent amount of carbon derived from cellulose nanofibers and the atomic equivalent amount of carbon derived from the water-soluble carbon material, i.e., the sum of the amount of carbon derived from cellulose nanofibers and the amount of carbon derived from the water-soluble carbon material, is preferably 1.0 mass% to 10.0 mass%, more preferably 1.5 mass% to 7.0 mass%, and even more preferably 2.0 mass% to 5.0 mass%, based on 100 mass% of particles (B).

[0046] From the viewpoint of effectively achieving both high energy density and excellent safety, the content of component (B) (particles (B)) in the positive electrode active material for a lithium ion secondary battery of the present invention is 10 mass % to 30 mass %, preferably 10 mass % to 20 mass %, and more preferably 15 mass % to 20 mass %.

[0047] In addition, when component (B) (particle (B)) has carbon derived from cellulose nanofibers and / or carbon derived from a water-soluble carbon material supported on its surface, the content of component (B) (particle (B)) includes the amount of these carbons supported. In addition, the atomic equivalent amount (supported amount) of carbon derived from cellulose nanofibers present in particle (B) and the atomic equivalent amount (supported amount) of carbon derived from water-soluble carbon material are values ​​determined by measurement using a carbon / sulfur analyzer.

[0048] The particles (B) can be obtained, for example, by the following production method. Specifically, the method comprises the following steps (Ib) to (IVb): (Ib) A step of adding a lithium compound, a manganese compound and / or an iron compound, a phosphate compound, cellulose nanofibers, and water to obtain a slurry water b, and then subjecting the slurry water to a hydrothermal reaction to obtain a composite B. (IIb) A step of adding the obtained composite B, an acrylic acid (co)polymer or a salt thereof x, nano resin particles y having an average particle size of 10 nm to 150 nm, and water to obtain a slurry water c. (IIIb) A step of subjecting the obtained slurry water c to spray drying to obtain granules Z. (IVb) A step of firing the obtained granules Z Equipped with In this production method, the nano resin particles y are one or more selected from polystyrene particles, polymethyl methacrylate particles, and polylactic acid particles.

[0049] The above step (Ib) is a step of obtaining a composite B by adding a lithium compound, a manganese compound, an iron compound, a phosphate compound, and water to obtain a slurry water b, which is then subjected to a hydrothermal reaction.

[0050] As the lithium compound, the same ones as those for the above particles (A) can be used, with hydroxides being preferred. As the manganese compound, the same ones as those for the above particles (A) can be used. Examples of the iron compound include iron acetate, iron nitrate, iron sulfate, etc. These may be used alone or in combination of two or more. Among these, iron sulfate is preferred from the viewpoint of improving the battery characteristics. In addition to these manganese compounds and iron compounds, metals other than manganese compounds and iron compounds (M 2 ) compounds may also be used. Examples of phosphoric acid compounds include orthophosphoric acid (H3PO4, phosphoric acid), metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, etc. Among these, it is preferable to use phosphoric acid, and it is preferable to use it as an aqueous solution with a concentration of 70% by mass to 90% by mass. In addition, when supporting carbon derived from cellulose nanofibers, cellulose nanofibers may be added together with a lithium compound and the like in step (Ib) to obtain slurry water b.

[0051] More specifically, the step (Ib) includes a step (ib-1) of mixing a phosphoric acid compound with a slurry water b' containing a lithium compound to obtain a composite B'; A step (ib-2) of subjecting the obtained composite B' and slurry water b containing metal compounds including at least a manganese compound and an iron compound to a hydrothermal reaction to obtain composite B. It is preferable to provide: When cellulose nanofibers are used, a slurry water b' containing a lithium compound and cellulose nanofibers may be prepared.

[0052] In the step (ib-1), the content of the lithium compound in the slurry water b' is preferably 5 to 50 parts by mass, and more preferably 7 to 45 parts by mass, based on 100 parts by mass of water. When cellulose nanofibers are used, the content thereof in the slurry water b' is preferably 0.2 to 10.6 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 0.8 to 5.3 parts by mass, calculated as the amount of residue from the carbonization treatment, per 100 parts by mass of water. It is preferable to stir the slurry water b' before adding the phosphoric acid compound to the slurry water b'. The stirring time of the slurry water b' is preferably 1 to 15 minutes, more preferably 3 to 10 minutes. The temperature of the slurry water b' is preferably 20°C to 90°C, more preferably 20°C to 70°C.

[0053] In the step (Ib), when phosphoric acid is mixed with the slurry water b', it is preferable to drop phosphoric acid while stirring the slurry water. The dropping speed of phosphoric acid into the slurry water b' is preferably 15 mL / min to 50 mL / min, more preferably 20 mL / min to 45 mL / min, and even more preferably 28 mL / min to 40 mL / min. The stirring time of the slurry water b while dropping phosphoric acid is preferably 0.5 hours to 24 hours, and more preferably 3 hours to 12 hours. The stirring speed of the slurry water while dropping phosphoric acid is preferably 200 rpm to 700 rpm, more preferably 250 rpm to 600 rpm, and even more preferably 300 rpm to 500 rpm. When the slurry water b' is stirred, it is preferable to cool the slurry water b' to a temperature equal to or lower than the boiling point of the slurry water b'. Specifically, it is preferable to cool the slurry water b' to a temperature equal to or lower than 80°C, and more preferably to a temperature in the range of 20°C to 60°C.

[0054] The slurry water b' after mixing with the phosphoric acid compound preferably contains 2.0 to 4.0 moles of lithium per mole of phosphoric acid, more preferably 2.0 to 3.1 moles, and the lithium compound and the phosphoric acid compound may be used in such amounts. More specifically, the slurry water b' after mixing with the phosphoric acid compound preferably contains 2.7 to 3.3 moles of lithium per mole of phosphoric acid, more preferably 2.8 to 3.1 moles.

[0055] By purging nitrogen into the slurry water b' after mixing with the phosphoric acid compound, the reaction in the slurry water is completed, and a composite B', which is a precursor of the particles (B), is obtained as a slurry. When nitrogen is purged, the reaction can proceed in a state where the dissolved oxygen concentration in the slurry water b' is reduced, and the dissolved oxygen concentration of the resulting slurry water containing the composite B' is also effectively reduced, so that the oxidation of the metal compound to be added in the next step can be suppressed. In the slurry water b' containing the composite B', the precursor of the particles (B) exists as fine dispersed particles. The composite B' is obtained as a composite of trilithium phosphate (Li3PO4) and cellulose nanofibers.

[0056] Next, in step (ib-2), the complex B' obtained in step (ib-1) and the slurry water b containing metal compounds including at least a manganese compound and an iron compound are subjected to a hydrothermal reaction to obtain a complex B.

[0057] The molar ratio of the manganese compound to the iron compound (manganese compound:iron compound) used is preferably 20:80 to 90:10, more preferably 25:75 to 85:15, and further preferably 30:70 to 80:20. The total amount of these metal compounds added is preferably 0.99 mol to 1.01 mol, more preferably 0.995 mol to 1.005 mol, per mol of phosphate ions contained in the slurry water A.

[0058] The amount of water used in the hydrothermal reaction is preferably 10 mol to 50 mol, and more preferably 12.5 mol to 45 mol, per mol of phosphate ion contained in the slurry water b, from the viewpoints of the solubility of the metal compound, ease of stirring, synthesis efficiency, and the like.

[0059] Manganese compounds, iron compounds and metals (M 2The order of addition of the metal compounds is not particularly limited. In addition to adding these metal compounds, an antioxidant may be added if necessary. As such an antioxidant, sodium sulfite (Na2SO3), sodium hydrosulfite (Na2S2O4), aqueous ammonia, etc. can be used. The amount of the antioxidant to be added is determined based on the amount of the manganese compound, the iron compound, and the metal (M 2 The amount is preferably 0.01 mol to 1 mol, and more preferably 0.03 mol to 0.5 mol, relative to 1 mol of the total of the salts.

[0060] Manganese compounds, iron compounds and metals (M 2 The content of complex B' in the slurry water b obtained by adding the above-mentioned fluorine-containing compound and, if necessary, an antioxidant, etc., is preferably 10 to 50 mass %, more preferably 15 to 45 mass %, and even more preferably 20 to 40 mass %.

[0061] The hydrothermal reaction may be carried out at 100° C. or higher, preferably at 130° C. to 200° C. The hydrothermal reaction is preferably carried out in a pressure-resistant vessel, and when the reaction is carried out at 130° C. to 200° C., the pressure is preferably 0.3 MPa to 1.6 MPa, and when the reaction is carried out at 140° C. to 160° C., the pressure is preferably 0.3 MPa to 0.6 MPa. The hydrothermal reaction time is preferably 0.1 hours to 48 hours, more preferably 0.2 hours to 24 hours. The obtained complex B is isolated by filtration, washing with water, and drying. The drying method used may be freeze drying or vacuum drying.

[0062] The above step (IIb) is a step of obtaining slurry water c by adding the complex B obtained in step (Ib), acrylic acid (co)polymer or its salt x, nano resin particles y having an average particle size of 10 nm to 150 nm, and water, and one or more kinds selected from polystyrene particles, polymethyl methacrylate particles, and polylactic acid particles are used as the nano resin particles y. In this way, by preparing slurry water using the complex B obtained in step (Ib), acrylic acid (co)polymer or its salt x, and nano resin particles y of fine particles, physical and electrical effects can be exerted to separate the particles (B) while suppressing their aggregation, and it is also possible to produce particles having large depressions on the surface as part of the particles (B) obtained after going through steps (IIIb) to (IVb) described later.

[0063] The acrylic acid (co)polymer or its salt x adheres to the surface of the particles (B) and can effectively suppress aggregation of the particles (B) by physical and electrical actions. The mass average molecular weight of the acrylic acid (co)polymer or its salt x is preferably 1,000 to 200,000, more preferably 1,000 to 150,000, and even more preferably 1,000 to 100,000, from the viewpoint of effectively suppressing aggregation between the particles (B).

[0064] Specific examples of the acrylic acid (co)polymer or its salt x include one or more selected from sodium polyacrylate, ammonium polyacrylate, sodium salt of acrylic acid / maleic acid copolymer, and sodium salt of acrylic acid / acrylamide / sulfonic acid copolymer. Among them, sodium polyacrylate is preferred from the viewpoint of effectively increasing the dispersibility of the slurry water b.

[0065] The amount of the acrylic acid (co)polymer or its salt x added is preferably 0.01 to 1.5 parts by mass, more preferably 0.05 to 1.5 parts by mass, and even more preferably 0.1 to 1.5 parts by mass, relative to 100 parts by mass of the complex B.

[0066] The nano-resin particles y enter the gaps between the particles (B) and can further separate the particles (B) from each other, while also increasing the fluidity of the slurry water, making it easier to form depressions on the particle surfaces. The nano-resin particles y include one or two types selected from polystyrene particles, polymethyl methacrylate particles, and polylactic acid particles, and polystyrene particles are preferred from the viewpoint of efficiently producing particles having large depressions on their surfaces.

[0067] The amount of the nano resin particles y added is preferably 0.5 to 15 parts by mass, more preferably 1 to 12 parts by mass, and even more preferably 2 to 10 parts by mass, relative to 100 parts by mass of the composite B.

[0068] The mass ratio (x / y) of the amount of acrylic acid (co)polymer or its salt x to the amount of nano resin particles y is preferably 0.002 to 3.0, more preferably 0.033 to 1.0, and further preferably 0.05 to 0.2.

[0069] The solid content concentration of the slurry water c is preferably 5% by mass to 30% by mass, more preferably 5% by mass to 20% by mass, and further preferably 5% by mass to 15% by mass.

[0070] After adding water, it is preferable to pre-stir the slurry water c before proceeding to step (IIIb). The stirring time of the slurry water c is preferably 3 to 60 minutes, more preferably 5 to 30 minutes. The temperature of the slurry water c is preferably 10°C to 60°C, more preferably 20°C to 40°C.

[0071] The above step (IIIb) is a step of subjecting the slurry water c obtained in the step (IIb) to spray drying to obtain the granules Z. In the spray drying, the operating conditions may be appropriately set depending on the apparatus used. For example, the treatment conditions for a micromist dryer equipped with a four-fluid nozzle (MDL-050M manufactured by Fujisaki Electric Co., Ltd.) are such that the hot air temperature is preferably 110° C. to 300° C., and more preferably 150° C. to 250° C. The volume ratio of the supply amount of hot air to the supply amount of slurry water (supply amount of hot air / supply amount of slurry water) is preferably 500 to 10,000, and more preferably 1,000 to 9,000.

[0072] By obtaining the granules Z in the step (IIIb), it becomes possible to effectively include particles having one or two large depressions on the surface as part of the particles obtained through the subsequent step (IVb). That is, the slurry water c is first sprayed and turned into droplets by spray drying, and the particles (B) are uniformly dispersed in the water in the droplets. Next, when heat is applied to the droplets in this state, the water on the droplet surface evaporates, and the water present in the center of the droplet moves to the droplet surface and then evaporates. In this way, when the water moves from the center to the surface in the droplet, the particles (B) move to the droplet surface together with the water, and the state transitions to a state in which the particles (B) are distributed in large amounts on the surface. When this state is reached, the water still remaining in the center of the droplet has nowhere to go when it is subsequently dried, and breaks part of the layer of the particles (B) on the droplet surface and evaporates. The traces of the evaporation of the water in the center appear as depressions in the granules Z, and later, through the process (IVb) described below, these depressions form large depressions on the surface of the particles.

[0073] The step (IVb) is a step of calcining the granules Z obtained in the step (IIIb). The calcination conditions in the step (IVb) are preferably a reducing atmosphere or an inert atmosphere, the calcination temperature is preferably 500° C. to 1000° C., more preferably 550° C. to 900° C., and the calcination time is preferably 0.5 hours to 12 hours, more preferably 1 hour to 6 hours.

[0074] The positive electrode active material for a lithium ion secondary battery of the present invention contains, as component (C), particles represented by the following formula (c) and having an average particle size of 2 μm to 8 μm in an amount of 5% by mass to 40% by mass. LiM 3 y Co j O2···(c) (In formula (c), M 3 represents one or more elements selected from Ni, Mn, Al, Mg, Ti, V, Cr, Fe, Zr, Ga, and Si. y and j are numbers satisfying 0 ≦ y ≦ 0.1, 0 < j ≦ 1, and (valence of M 3 ) × y + 3j = 3.)

[0075] The particles represented by the above formula (c) of component (C) (hereinafter also referred to as "particles (C)") are particles having a crystal structure of a layered rock salt type structure. By containing such particles (C) having a specific average particle size in the above amount, while maintaining high safety, the voids between the particles with the above components (A) and (B) can be effectively reduced, and the energy density can be effectively increased.

[0076] From the viewpoint of effectively increasing the energy density, the particles (C) represented by the above formula (c) are preferably those in which M 3 is one or more elements selected from Ni and Mn, and more preferably 50 mol% or more of M 3 is Ni. Specifically, LiCoO2, LiMn 0.05 Co 0.95 O2, LiAl 0.05 Co 0.95 O2, LiMg 0.03 Co 0.98 O2, LiSi 0.03 Co 0.96 O2 can be used. Among them, LiCoO2 is preferable.

[0077] The average particle size of the particles (C) is 2 μm to 8 μm, more preferably 2 μm to 6 μm, from the viewpoints of effectively achieving compatibility with high energy density while ensuring excellent safety and from the viewpoint of handling. Here, the "average particle size" of the particles (C) is the D obtained from the volume-based particle size distribution based on the laser diffraction / scattering method. 50 The values ​​shown are the particle diameters (median diameters) at 50% of the cumulative particle size.

[0078] From the viewpoint of effectively achieving both high energy density and excellent safety, the content of component (C) (particles (C)) in the positive electrode active material for a lithium ion secondary battery of the present invention is 5 mass % to 40 mass %, preferably 8 mass % to 30 mass %, and more preferably 10 mass % to 20 mass %.

[0079] The particles (C) can be obtained, for example, by the production method described in the Examples. Specifically, the manufacturing method includes steps of adding a lithium compound and a cobalt compound, pulverizing and mixing them in a ball mill, calcining the mixture, and then calcining the mixture. Examples of the lithium compound to be used include hydroxides (e.g., LiOH·H2O, LiOH), carbonates, acetates, and nitrates. Of these, carbonates are preferred. Examples of the cobalt compound include cobalt acetate, cobalt nitrate, and cobalt oxide. These may be used alone or in combination of two or more. Among these, cobalt oxide is preferred from the viewpoint of improving the battery characteristics. In addition to these lithium compounds and cobalt compounds, metals other than these compounds (M 3 ) compounds may also be used. When firing, it is preferable to first perform pre-firing at 500° C. to 1000° C., preferably 600° C. to 900° C., for 1 hour to 15 hours, preferably 1 hour to 10 hours, and then perform main firing at 500° C. to 1100° C., preferably 600° C. to 1000° C., for 5 hours to 20 hours, preferably 8 hours to 15 hours. In addition, it is preferable to crush the material after pre-firing before performing main firing.

[0080] The positive electrode active material for lithium ion secondary batteries of the present invention can be obtained by adjusting the amount of the particles of the above-mentioned components (A), (B), and (C) to the above-mentioned content, and then mixing them by a conventional method. There is no particular restriction on the order of adding the particles of the components (A), (B), and (C).

[0081] In the positive electrode active material for a lithium ion secondary battery of the present invention, from the viewpoint of increasing the compaction degree and effectively improving the energy density, the compaction degree under a load of 20 kN is preferably 3.3 g / cm 3 ~5.0g / cm 3 and more preferably 3.5 g / cm 3 ~5.0g / cm 3 and more preferably 4.0 g / cm 3 ~5.0g / cm 3 It is.

[0082] The positive electrode active material for lithium ion secondary batteries of the present invention can be used as a positive electrode material to construct a lithium ion secondary battery essentially consisting of a positive electrode, a negative electrode, an electrolyte, and a separator, or a positive electrode, a negative electrode, and a solid electrolyte. Specifically, for example, the positive electrode active material for lithium ion secondary batteries of the present invention is kneaded with acetylene black, ketjen black, polyvinylidene fluoride, N-methyl-2-pyrrolidone, or the like to prepare a positive electrode slurry, which is then applied to a current collector and press-molded to produce a positive electrode. In the positive electrode active material for a lithium ion secondary battery of the present invention, the above-mentioned three specific types of particles (A) to (C) are closely associated with each other, and are easily compacted during press molding to increase the electrode density, thereby making it possible to obtain a highly useful positive electrode that can effectively improve the rate characteristics and cycle characteristics.

[0083] Here, the negative electrode is not particularly limited in terms of its material composition, and any known material composition can be used, as long as it can absorb lithium ions during charging and release them during discharging. For example, lithium metal, graphite, silicon-based (Si, SiOx), lithium titanate, or carbon materials such as amorphous carbon can be used. It is preferable to use an electrode formed of an intercalation material capable of electrochemically absorbing and releasing lithium ions, particularly a carbon material. Furthermore, two or more of the above negative electrode materials may be used in combination, and for example, a combination of graphite and silicon-based materials can be used.

[0084] The electrolyte solution is prepared by dissolving a supporting salt in an organic solvent. The organic solvent is not particularly limited as long as it is an organic solvent that is usually used in electrolytes for lithium ion secondary batteries, and examples of the organic solvent that can be used include carbonates, halogenated hydrocarbons, ethers, ketones, nitriles, lactones, and oxolane compounds.

[0085] The supporting salt is not particularly limited in type, but is preferably at least one of inorganic salts selected from LiPF6, LiBF4, LiClO4, and LiAsF6, derivatives of such inorganic salts, organic salts selected from LiSO3CF3, LiC(SO3CF3)2, LiN(SO3CF3)2, LiN(SO2C2F5)2, and LiN(SO2CF3)(SO2C4F9), and derivatives of such organic salts.

[0086] The separator serves to electrically insulate the positive and negative electrodes and to retain the electrolyte, and may be, for example, a porous synthetic resin film, particularly a porous film of a polyolefin polymer (polyethylene, polypropylene).

[0087] The solid electrolyte electrically insulates the positive and negative electrodes and exhibits high lithium ion conductivity. 0.51 Li 0.34 TiO 2.94 , Li 1.3 Al 0.3 Ti 1.7(PO4)3, Li7La3Zr2O 12 , 50Li4SiO4 50Li3BO3, Li 2.9 PO 3.3 N 0.46 , Li 3.6 S 0.6 P 0.4 O4, Li 1.07 Al 0.69 Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, 30Li2S 26B2S3 44LiI, 63Li2S 36SiS2 1Li3PO4, 57Li2S 38SiS2 5Li4SiO4, 70Li2S 30P2S5, 50Li2S 50GeS2, Li7P3S 11 , Li 3.25 P 0.95 Just use S4.

[0088] The shape of the lithium ion secondary battery having the above-mentioned configuration is not particularly limited, and may be various shapes such as a coin type, a cylindrical type, a square type, or an irregular shape enclosed in a laminate exterior body. EXAMPLES

[0089] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples.

[0090] Particles of each component were produced according to the description of each production example. The physical properties of the particles (B) were measured according to the following methods.

[0091] <Measurement of the most common cavity diameter and cavity volume> For the particles (B), measurements were performed by mercury intrusion porosimetry using a measuring device (AutoPore IV9520, manufactured by Micromeritics). A Model 08 (manufactured by Micromeritics) was used as the sample cell, and measurements were performed with the surface tension of mercury set at 485 dynes / cm and the contact angle of mercury set at 130°. The measurement pressure range was 0.1 to 60,000 psia. The peak value of the obtained pore size distribution diagram was taken as the most frequent value of the pit diameter, and the peak area was taken as the pit volume.

[0092] <<Measurement of the average particle size of primary particles>> The measurements were carried out using an X-ray diffraction apparatus (D8 ADVANCE A-25, manufactured by Bruker AXS). The measurement conditions were as follows: target CuKα, tube voltage 50 kV, tube current 350 mA, scanning range 10 to 80° (2θ), step width 0.0234°, and scan speed 0.13° / step. The XRD pattern was analyzed using the XRD / Lebert method to calculate the crystallite diameter, and this value was used as the average particle diameter of the primary particles.

[0093] <<Measurement of average particle size (secondary particles)>> The particle size distribution of the particles was measured using a laser diffraction device (Microtrac MT3000II, manufactured by MicrotracBEL). The measurement conditions were as follows: particle transmittance: transmission, particle shape: non-spherical, particle refractive index: 1.52. Ethanol was used as the solvent, and the solvent refractive index: 1.36. The average particle size of the particles (C) was determined by this measurement method.

[0094] <<Measurement of compaction density>> The density of the particles (B) and the obtained positive electrode active material was measured using a low resistivity meter (MCP-T610, manufactured by Mitsubishi Analytech Co., Ltd.) when a load of 20 kN was applied.

[0095] <<Measurement of the proportion of lithium-based polyanion particles having depressions>> Particles (B) were observed by SEM, and 10 images were taken of different fields of view. A total of about 300 particles (B) were visually recognized in each image. Particles having 1 to 2 dents with a diameter of 1.0 μm or more on the surface were counted as "particles (B) having 1 to 2 dents formed on the surface", and the number of particles was counted. The value (%) of {(number of particles having 1 to 2 dents with a diameter of 1.0 μm or more on the surface) / (total number of particles (B) having a diameter of 5.0 μm or more)}×100 was calculated, and this value was defined as the "particle number ratio of particles (B) having 1 to 2 dents formed on the surface (particle number ratio of dent particles)".

[0096] [Production Example 1: Production of Particles (A) (NCM Particles)] 473 g of nickel sulfate hexahydrate, 169 g of cobalt sulfate heptahydrate, 145 g of manganese sulfate pentahydrate, and 3 L of water were mixed so that the molar ratio of Ni:Co:Mn was 6:2:2, and then 25% ammonia water was added dropwise to the mixture at a rate of 300 mL / min to obtain a slurry a1 containing a metal composite hydroxide having a pH of 11. Next, the slurry a1 was filtered and dried to obtain a mixture b1 of metal composite hydroxides, and then 37 g of lithium carbonate was mixed with the mixture b1 in a ball mill to obtain a powder mixture c1. The obtained powder mixture c1 was pre-calcined at 800°C for 4 hours in an air atmosphere and crushed, and then calcined at 800°C for 11 hours in an air atmosphere as a main calcination to obtain particles (A) (LiNi 0.6 Co 0.2 Mn 0.2 O2, average particle size of primary particles: 250 nm, average particle size of particles (A): 11.8 μm) were obtained.

[0097] [Production Example 2: Production of particles (B1) (LMFP particles)] LiOH·H2O 1272g and water 4L were mixed to obtain slurry x1. Next, 1153g of 85% phosphoric acid aqueous solution was dropped at 35mL / min into the obtained slurry x1 while stirring for 3 minutes while maintaining the temperature at 25°C, followed by adding 5892g of cellulose nanofiber (Wma-10002, Sugino Machine Co., Ltd., fiber diameter 4-20nm) and stirring at a speed of 400 rpm for 12 hours to obtain slurry y1 containing Li3PO4. The obtained slurry y1 was purged with nitrogen to adjust the dissolved oxygen concentration of the slurry y1 to 0.5mg / L, and then 1688g of MnSO4·5H2O and 834g of FeSO4·7H2O were added to the total amount of slurry y1 to obtain slurry z1. The molar ratio of added MnSO4 and FeSO4 (manganese compound: iron compound) was 70:30.

[0098] The obtained slurry z1 was then placed in an autoclave and subjected to a hydrothermal reaction at 170°C for 1 hour. The pressure inside the autoclave was 0.8MPa. After the hydrothermal reaction, the generated crystals were filtered and then washed with 12 parts by mass of water per part by mass of the crystals. The washed crystals were freeze-dried at -50°C for 12 hours to obtain a complex Cz1. 1000g of the obtained complex Cz1 was taken out and 1L of water was added thereto to obtain a slurry Ez1. The obtained slurry Ez1 was dispersed for 1 minute with an ultrasonic agitator (T25, manufactured by IKA Co., Ltd.) to uniformly color the entire mixture, and then spray-dried (nozzle air flow rate 35L / min, supply air temperature 180°C) using a spray dryer (MDL-050M, manufactured by Fujisaki Electric Co., Ltd.) to obtain a granule Fz1. The obtained granules Fz1 were calcined at 700°C for 1 hour in an argon-hydrogen atmosphere (hydrogen concentration 3%) to obtain particles (B1) (LiMn 0.7 Fe 0.3 PO4, carbon loading: 2.0 mass%, average particle size of primary particles: 100 nm, average particle size of particles (B1): 15.8 μm) was obtained. In the obtained particle (B1), the most frequent pit diameter measured by mercury intrusion porosimetry was 1.50 μm, the pit volume was 0.44 mL / g, and the compaction degree was 3.1 g / cm. 3 The percentage of particles having one or two depressions on the surface was 72%. An SEM photograph of the obtained particles (B1) is shown in FIG.

[0099] [Production Example 3: Production of particles (B2) (LMFP particles)] In Production Example 2, the amount of MnSO4·5H2O was changed from 1688 g to 723 g, and the amount of FeSO4·7H2O was changed from 834 g to 1946 g relative to the total amount of the slurry y1. 0.3 Fe 0.7 PO4, carbon loading: 2.0 mass%, average particle size of primary particles: 100 nm, average particle size of particles (B2): 13.3 μm) was obtained. In the obtained particle (B2), the most frequent pit diameter measured by mercury intrusion porosimetry was 1.67 μm, the pit volume was 0.48 mL / g, and the compaction degree was 3.0 g / cm. 3 The percentage of particles having one or two depressions on the surface was 65%.

[0100] [Production Example 4: Production of particles (B3) (LMFP particles)] In Production Example 2, the amount of MnSO4·5H2O was changed from 1688 g to 241 g, and the amount of FeSO4·7H2O was changed from 834 g to 2502 g relative to the total amount of the slurry y1. 0.1 Fe 0.9 PO4, carbon loading: 2.0 mass%, average particle size of primary particles: 100 nm, average particle size of particles (B3): 12.7 μm) was obtained. In the obtained particle (B3), the most frequent pit diameter measured by mercury intrusion porosimetry was 1.41 μm, the pit volume was 0.40 mL / g, and the compaction degree was 3.0 g / cm. 3 The percentage of particles having one or two depressions on the surface was 69%.

[0101] [Production Example 5: Production of particles (B4) (LMFP particles)] In the granulation step using a spray dryer (MDL-050M, manufactured by Fujisaki Electric Co., Ltd.) in Production Example 2, the operating conditions of the spray dryer were changed from a nozzle air flow rate of 35 L / min, a slurry flow rate of 30 mL / min, and an inlet air temperature of 200°C to a nozzle air flow rate of 5 L / min, a slurry flow rate of 60 mL / min, and an inlet air temperature of 200°C. In the same manner as in Production Example 2, particles (B4) (LiMn 0.7 Fe 0.3 PO4, carbon loading: 2.0 mass%, average particle size of primary particles: 100 nm, average particle size of particles (B4): 31.2 μm) was obtained. In the obtained particle (B4), the most frequent pit diameter measured by mercury intrusion porosimetry was 6.81 μm, the pit volume was 20.3 mL / g, and the compaction degree was 2.2 g / cm. 3 The percentage of particles having one or two depressions on the surface was 54%.

[0102] [Production Example 6: Production of Particles (C) (LCO Particles)] Powder mixture C1 was prepared by mixing 222 g of lithium carbonate and 482 g of cobalt oxide in a ball mill so that the molar ratio of Li:Co was 1:1. Powder mixture C1 was molded under a molding pressure of 500 kg / cm 3 The compact was then compressed and molded under a pressure of 1000 kg / cm and pre-sintered at 700°C for 5 hours in an air atmosphere. 3 After compacting, the mixture was sintered at 900°C for 10 hours in an air atmosphere to obtain particles (C) (LiCoO2, average particle size: 5.4μm).

[0103] [Examples 1 to 4, Comparative Examples 1 to 7] According to the formulation shown in Table 1, particles of each component were mixed using a pestle and mortar to obtain a positive electrode active material. Next, the obtained positive electrode active material was used to carry out various evaluations according to the following methods. The results are shown in Table 1.

[0104] <<Measurement of compaction density>> The density of the obtained positive electrode active material was measured under a load of 20 kN using a low resistivity meter (MCP-T610, manufactured by Mitsubishi Analytech Co., Ltd.) in the same manner as for the particles (B).

[0105] Calculating energy density per volume The obtained positive electrode active materials were used as positive electrode materials to prepare positive electrodes for lithium ion secondary batteries. Specifically, the obtained positive electrode active materials, Ketjen black, and polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, and N-methyl-2-pyrrolidone was added to the mixture and thoroughly kneaded to prepare a positive electrode slurry. The positive electrode slurry was applied to a current collector made of aluminum foil with a thickness of 20 μm using a coater, and vacuum dried at 80° C. for 12 hours. After that, the mixture was pressed at 20 kN using a roll press and punched into a disk shape with a diameter of 14 mm to form a positive electrode.

[0106] Next, a coin-type secondary battery was constructed using the above positive electrode. A lithium foil punched to φ15 mm was used as the negative electrode. The electrolyte was a mixed solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7, in which LiPF6 was dissolved at a concentration of 1 mol / L. A polymer porous film was used as the separator. These battery components were assembled and housed in an atmosphere with a dew point of -50°C or less by a conventional method, to obtain a coin-type secondary battery (CR-2032).

[0107] Using the obtained coin-type secondary battery, the discharge capacity of 0.2 C (34 mAh / g) was measured in an environment at an air temperature of 30° C. using a discharge capacity measuring device (HJ-1001SD8, manufactured by Hokuto Denko Corporation). Next, the electrode density was calculated by the following formula (x), and this was introduced into the following formula (y) to calculate the energy density per volume. Electrode density (g / cm 3 )= Mass of positive electrode active material in positive electrode (mg) / electrode volume (φ14mm x thickness (μm)) (x) Positive electrode volumetric energy density at 30℃ (Wh / L) = Discharge capacity at 30℃ (mAh / g) × average voltage (V) × electrode density (g / cm3 ) (y)

[0108] <Safety evaluation (DSC peak temperature measurement)> Using each of the obtained positive electrode active materials, a DSC curve was obtained in a temperature range of 30° C. to 500° C. by measurement using a differential scanning calorimeter (DSC404 F3, manufactured by NETZSCH). At that time, the measurement was performed by placing about 10 mg of the sample in an aluminum pan, and the heating rate was 10° C. / min. Next, the obtained DSC curve was observed to determine the exothermic peak temperature. The higher the exothermic peak temperature, the more excellent the safety can be evaluated.

[0109] [Table 1]

Claims

1. The following components (A), (B), and (C): (A) Particles represented by the following formula (a) and having an average particle size of 5 μm to 15 μm: 40% by mass to 85% by mass LiNi a Co b Mn c M 1 w O 2 ...(a) (In formula (a), M 1 represents one or more elements selected from Mg, Ti, Nb, Fe, Cr, Si, Al, Ga, V, Zn, Cu, Sr, Mo, Zr, Sn, Ta, W, La, Ce, Pb, Bi, and Ge. a, b, c, and w are within the range of 0.3≦a<1, 0<b≦0.7, 0<c≦0.7, and 0≦w≦0.3, and 3a+3b+3c+(M 1 (valence of x) × w = 3. (B) A particle aggregate containing particles represented by the following formula (b) and having an average particle size of 12 μm to 25 μm, with one to two depressions formed on the surface: 10% by mass to 30% by mass Li f Mn g Fe h M 2 x P.O. 4 ...(b) (In formula (b), M 2 represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd. f, g, h, and x satisfy 0<f≦1.2, 0.3≦g≦1.2, 0.2≦h≦1.2, 0≦x≦0.3, and 3 / 7≦g / h≦4, and f+(valence of Mn)×g+(valence of Fe)×h+(valence of Mn)×g+(valence of Mn). 2 (valence of x) × x = 3. (C) Particles represented by the following formula (c) and having an average particle size of 2 μm to 8 μm: 5% by mass to 40% by mass LiM 3 y Co j O 2 ...(c) (In formula (c), M 3 represents one or more elements selected from Ni, Mn, Al, Mg, Ti, V, Cr, Fe, Zr, Ga, and Si. y and j are each 0≦y≦0.1, 0<j≦1, and (M 3 (valence of y) × y + 3j = 3. A positive electrode active material for a lithium ion secondary battery, comprising components (A), (B), and (C) mixed together in an amount of: In component (B), the most frequent pit diameter as a whole is 1.0 μm to 2.5 μm, the pit volume is 0.3 mL / g to 0.8 mL / g, and the compaction degree under a load of 20 kN is 2.9 g / cm 3 to 3.3 g / cm 3 , as measured by mercury intrusion porosimetry; the ratio of particles having one or two depressions on their surfaces to the number of particles in component (B) is 55% to 100%; Carbon derived from cellulose nanofibers and / or carbon derived from a water-soluble carbon material is supported on the surface of particles of component (B); and A positive electrode active material for a lithium ion secondary battery, having a compaction density at a load of 20 kN of 3.5 g / cm 3 to 5.0 g / cm 3 .

2. A positive electrode active material for a lithium ion secondary battery as described in claim 1, wherein the total amount of carbon derived from cellulose nanofibers and carbon derived from the water-soluble carbon material supported on the surface of the particles of component (B) is 1.0 mass % to 10.0 mass % in 100 mass % of component (B).

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery

    JP2014060020A

  • Lithium ion battery

    JP2014192142A

  • Lithium ion secondary battery

    JP2016076317A